Answer:
x = -2
Step-by-step explanation:
The initial expression is:
10( x + 3) - ( -9x - 4) = x - 5 + 3
To solve for x, we first need to apply the distributive property as:
10x + 10(3) -(-9x) - (-4) = x - 5 + 3
10x + 30 + 9x + 4 = x - 5 + 3
Then, add the like terms to get:
(10x + 9x) + (30 + 4) = x + (-5 + 3)
19x + 34 = x - 2
Subtract x from both sides:
19x + 34 - x = x - 2 - x
18x + 34 = -2
Subtract 34 from both sides:
18x + 34 - 34 = -2 - 34
18x = -36
Finally, divide both sides by 18:
18x/18 = -36/18
x = -2
Therefore, the answer is x = -2